Comparison of fasting and non-fasting lipid profile in Nigerian adults - Etaniamhe Orimadegun, Bose; Afolabi, Fateemah Oluwadamilola; Tijani, Bashar Adekilekun (International Journal of Research in Medical Sciences, 2025)
Background: Lipid profiles are a vital cardiovascular risk factor. Traditionally fasting lipid profiles are used to minimise postprandial variability, the necessity of fasting for accurate lipid assessment has been questioned, and its utility among Nigerian adults remains uncertain. We compared fasting and non-fasting plasma lipid levels in Nigerian adults to assess the practicality of a non-fasting lipid profile. Methods: We conducted this self-control comparative study at University College Hospital in Ibadan, Nigeria. We recruited 90 consenting adults aged 18 and older from various outpatient units. We collected plasma samples after an overnight fast and two hours post-prandial. We analysed the lipid levels using standard laboratory methods. We used paired t-tests and bland Altman graphs to compare mean values and determine agreement. Results: The fasting total cholesterol (TC) (5.25±2.05 mmol/l) and LDL cholesterol (3.84±2.08 mmol/l) levels were significantly higher than their non-fasting counterparts (3.95±1.79 mmol/l and 2.34±1.74 mmol/l, respectively; p<0.001). Conversely, triglyceride (TG) levels were significantly higher in the non-fasting state (1.68±0.88 mmol/l) compared to the fasting state (1.35±0.73 mmol/l; p<0.001). HDL cholesterol levels showed minimal differences between fasting and non-fasting conditions (p=0.136). Bland-Altman analysis indicated that the variations between fasting and non-fasting lipid profiles fell within clinically acceptable limits. Conclusions: Within the acceptable limits of agreement, non-fasting lipid profiles offer a practical alternative to fasting profiles for cardiovascular risk assessment in Nigerian adults.